Cellulosic Fabric Wastes Grafted with DMAEMA for the Removal of Direct Dyes - H.H. Sokker; E.S. Abdel Halim; A.S. Aly; A. Hashem (Adsorption Science & Technology)
Dimethylaminoethyl methacrylate (DMAEMA) was grafted onto a cellulosic fabric waste via γ-irradiation ( 60 Co). Factors affecting the grafting such as the radiation dose and monomer concentration were investigated. The grafted fabric waste was studied by infrared (FT-IR) spectroscopy and thermogravimetric analysis (TGA), as well as its surface morphology. The ability of the grafted fabric waste for removing Direct Violet 31 from its aqueous solution was studied by batch experiments. The adsorption data obeyed the Langmuir and Freundlich isotherms. It was found that 1 g of grafted fabric waste adsorbed 40 mg of Direct Violet 31 from its aqueous solution. The grafted fabric waste could be used as an adsorbent for water pollutants such as dyes, thereby solving one of the most important environmental problems of the textile industry.